Pengaruh Kinerja Orgasnisasi dan Kompetensi Karyawan terhadap Pencapaian Visi Misi - Aji Tuhagana; Rengga Madya Pranata; Hafsari Prabhamanik Faddila (Ebisnis Manajemen, 2025)
This study aims to analyze the influence of organizational performance and employee competency on the achievement of the vision and mission of Universitas Buana Perjuangan (UBP) Karawang. The research background stems from the importance of synergy between effective organizational governance and the quality of human resources in realizing the strategic direction of higher education. The study employed a quantitative approach with a survey method. Data were collected through questionnaires distributed to 78 respondents, consisting of lecturers and permanent education staff at UBP Karawang. Data analysis was performed using multiple linear regression with the assistance of SPSS. The results indicate that both organizational performance and employee competency have a positive and significant influence on the achievement of the university's vision and mission, both partially and simultaneously. Organizational performance exerts a more dominant influence than employee competency, with an R² value of 0.534, indicating that 53.4% ​​of the variation in vision and mission achievement is explained by these two variables. These findings confirm that effective governance, cross-unit coordination, and the development of professional competencies and work attitudes play a crucial role in improving institutional performance. The practical implication of this study is the need to strengthen quality management and develop sustainable competencies as key strategies in realizing the vision and mission of higher education.